Evaluating the summative effectiveness of a curriculum integrated STEM-based web research hub in fostering science literacy among junior high school students - Fikri Aulia; Affero Bin Ismail; Dadi Mulyadi; Rayendra Rayendra; Wikan Budi Utami (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2026)
The need for holistic STEM learning innovations is crucial to enhance students’ scientific literacy in the digital era. This RnD study aims to develop a web-based Research Hub as a technology-rich learning environment and evaluate its empirical impact on students’ scientific literacy. Utilizing the Lee & Owens framework, the study adopted a one-group pretest-posttest design to evaluate its effectiveness. The sample consisted of ninth-grade students from a junior high school in Malang Raya subjected to a two week intervention. Data werw collected using a 20 item two tier scientific literacy test adapted to the PISA 2022 framework. Descriptive statistics showed a positive shift in the mean score from 63.65 at pretest to 72.13 at posttest, yielding a mean difference gain of 8.48. Prerequisite testing confirmed that the dataset was normally distributed. The subsequent parametric Paired Sample T-Test demonstrated a highly significant increase in scientific literacy with , , 2, with a 95% Confidence Interval ranging from -9.465 to -7.503. Furthermore, calculating the magnitude of the intervention yielded an exceptionally large Cohen’s d effect size , proving that the integrated Research Hub framework provides substantial empirical power in advancing student competencies compared to traditional platform limits. In conclusion, the technology-rich Research Hub is highly effective, valid, and scalable in improving junior high school students’ scientific literacy within modern STEM education frameworks.